Utilization of Learning Videos During Covid 19 - Rezi, Melisa; Esha Okta Raudha; Rene Faruk Garzozi-Pincay; Jem Cloyd M. Tanucan (Journal International Inspire Education Technology, 2022)
Education is a place to gain knowledge and knowledge and to develop the creativity of students, and education is very important for life because with this education we can grasp the world. At the end of 2019 the world was shocked by a virus originating from Wuhan, China called the corona virus or covid 19, which has disrupted human health and has claimed many lives from around the world. And with this it has an impact on education and the economy in Indonesia. And with this, education came to a halt, so the government decided to switch face-to-face learning to online learning. The point is to break the chain of spread of covid 19, and in Indonesia the government is also implementing PSBB and issuing laws to prohibit Indonesian people from gathering and implementing social distancing. And the government also prohibits people from doing activities outside the home and is required to keep their distance. And with this pandemic, teachers are very much required to be able to teach online and be able to develop online teaching materials properly and efficiently, and to carry out online education learning using technology to communicate, one of which is whats 'ap and develop teaching materials using the kine application. Master for editing learning videos. The kine master application is an application that can be installed on laptops and on android, and this kine master application also has many interesting features and it is also easy to understand and use. For novice educators who want to edit videos, it is highly recommended to use the Kine Master application because it not only edits videos, but we can also create interesting animated videos.